Computer-based short term hydrothermal generation scheduling: article / Suhaimi Ishak - Ishak, Suhaimi
This paper presents a solution of a short term hydrothermal scheduling using Computer Approach and software MATLAB. The technique is used to handle the problems of short-term hydrothermal scheduling and economic load dispatch while satisfying and thermal constraints in order to minimize the total system cost.